(untitled) (Revista Espinhaço, 2020)
This paper aims to systematize the meaning of a great developmental project to the population of municipalities affected by the hydroelectric plant after its operation. The area flooded by the Irapé plant reached seven municipalities of the Jequitinhonha river upper course, Northeast of Minas Gerais, resulting in the relocation of approximately five thousand people and affecting thousands of inhabitants living in the lakeshore. The long resistance process of the affected population achieved fundamental rights throughout the relocation course; however, it did not impede the great socioeconomic, cultural and political losses that happened during the violent implantation, which sought to legitimize itself by the fact of the development promotion in the affected regions. From a qualitative methodology, we identified the consequences of the enterprise through interviews with representatives from different society sectors. The consequences caused by Irapé are diverse and complex. The dam changed the population’s relations with natural resources, frustrated different societal segments in terms of job creation, income and tourism, and strongly pressured ways of life into peasant communities.